(untitled) (Chittagong University Journal of Biological Sciences, 2013)
In the present investigation BR28 paddy was grown in the Boro season. Three herbicides: Rifit 500 EC, Ronstar 25 EC and Machete 5G were applied in different doses and studied their effects on the control of weeds and ultimate growth, yield and yield components of Boro paddy. Eleven different treatments viz.: T1 (control, no herbicide was used), T2 (only hand weeding was done), T3 (Rifit normal dose), T4 (double of Rifit normal dose), T5 (half of Rifit normal dose), T6 (Ronstar normal dose), T7 (double of Ronster normal dose), T8 (half of Ronster normal dose), T9 (normal dose of Machete), T10 (double of Machete normal dose) and T11 (half of Machete normal dose) were used in the experiment. The number of tillers, length per tiller, length per panicle, area of flag leaves, number of filled grains, percentage of filled grains, straw and grain yield per hectare were found maximum at T3 where normal dose of Rifit 500 EC was applied. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17077 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):01-10, 2011